Illocutionary act analysis of Encouragement Songs - Jarassri, Kaewmoon; Phennapha, Klaisingto (วารสารจิตวิทยาพุทธศาสตร์ประยุกต์เพื่อสังคม, 2020)
The objective is to analyze Illocutionary Act in lyrics with meanings of encouragement. This research was conducted using qualitative research methods. The data is collected from 23 encouragement songs that come from the song suggestion website which are in the form of clauses and sentences from the lyrics. The data will be analyzed according to the theory Illocutionary by Searle (1996). This research shows that there are three types of Illocutionary Act are found in the lyrics. They are Representative, Directive and Commissive. Representative is found the most common type of Illocutionary act with 47 data (44.33%) followed by Directive with 37 data (34.90%), and Commisive with 14 data (13.20%). There are also some sentences with more than 1 types of illocutionary act. There are 3 data (2.830%) of representative and directive and 3 data (2.830%) of directive and commissive, and the leas, there are 2 data (1.886%) representative and commissive. Encouragement songs tend to use storytelling, truth, experience, and imagination of the composers.